2018
DOI: 10.1002/anie.201806693
|View full text |Cite
|
Sign up to set email alerts
|

Annelated Cyclobutanes by Fe‐Catalyzed Cycloisomerization of Enyne Acetates

Abstract: Cationic Fe complexes of the general type [(Ph P) Fe(CO)(NO)]X (X=BF , BAr ) catalyze the redox-neutral cycloisomerization of 1,6- and 1,7-enyneacetates to afford bicyclic cyclobutanes under mild conditions in good yields and diastereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…1 b was synthesized in two steps according to the described in the literature procedure. [44] N-propargylamine (7.69 mL, 120 mmol, 1.00 eq.) was dissolved in dichloromethane (285 mL).…”
Section: Synthesis Of N-allyl-4-methyl-n-(prop-2-yn-1-yl)benzenesulfo...mentioning
confidence: 99%
“…1 b was synthesized in two steps according to the described in the literature procedure. [44] N-propargylamine (7.69 mL, 120 mmol, 1.00 eq.) was dissolved in dichloromethane (285 mL).…”
Section: Synthesis Of N-allyl-4-methyl-n-(prop-2-yn-1-yl)benzenesulfo...mentioning
confidence: 99%
“…Due to this restriction, photochemical [2 + 2] cycloaddition between two olefins is the most common strategy to form cyclobutanes. In 2018, the group of Plietker reported an unusual cycloisomerization of enynes using a cationic iron nitrosyl catalyst (Scheme 24) [61]. Their 1,6-and 1,7-enyneacetates were expected to isomerize to allenes, but instead isomerized to their corresponding bicyclo [3.…”
Section: Isomerizationsmentioning
confidence: 99%
“…catalyst (Scheme 24)[61]. Their 1,6-and 1,7-enyneacetates were expected to isomerize to allenes, but…”
mentioning
confidence: 99%
“…In 2016, Sheldrake demonstrated that aldehyde 14 reacted with diethylamine at room temperature using K 2 CO 3 as a base to form the bicyclic alkene 15 . Finally, in 2018, Plietker and co-workers developed a cyclization of substrates 16 in the presence of iron catalyst 17 into bicyclic products of type 18 …”
Section: Introductionmentioning
confidence: 98%